Penerapan Model Pembelajaran PBL Berbantuan Media Audio Visual Dalam Meningkatkan Keaktifan Belajar Siswa Pada Pembelajaran Matematika Di Sekolah Dasar - Febianti, Diah; Yantoro, Yantoro; Pamela, Issaura Sherly (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2024)
This research aims to describe the application of the Problem Based Learning (PBL) Model assisted by audio-visual media in increasing student learning activity in mathematics learning in elementary schools. The research was carried out using classroom action research (PTK) which consists of 2 cycles, namely cycle I and cycle II, where data collection uses observation in the form of teacher and student observations, interviews and documentation. This research uses the Taggart and Kemmis model which consists of 4 stages, namely the planning, implementation, observation and reflection stages. The data in this research were analyzed quantitatively and qualitatively. Based on the results of research conducted by applying the Problem Based Learning (PBL) learning model assisted by audio-visual media in mathematics learning, it can increase student learning activity. This can be seen from students experiencing increased activeness in learning by paying attention to each indicator of activeness in learning activities seen in each meeting cycle. In cycle I, meeting I was 50% and in meeting II it was 53%, an increase of 3%. In cycle II, meeting I was 86%. In meeting II it was 91%, an increase of 5%. Based on the research results, it can be concluded that the Problem Based Learning Model can increase student learning activity in Mathematics learning.